Determination of melamine in biscuits by high performance liquid chromatography - WEI Jin-mei; ZHANG Yong-mei; WANG Ji-qing; CAO Lu-xing; LUO Yu-zhu (浙江大学学报. 农业与生命科学版)
A high performance liquid chromatography method was developed for the determination of melamine in biscuits. The biscuit samples were extracted by 1% trichloroacetic acid solution and 2.2% lead acetate, and melamine was separated on a Hypersil ODS C18 column (100 mm×4.6 mm, 5 μm). Acetonitrile and sodium 1-octanesulfonate solution(pH 3) (15∶85, V/V) were used as mobile phase at a flow rate of 1.0 mL·min-1. The detective wavelength was set as 210 nm by an ultraviolet detector. The temperature of column was 40 ℃. The linear ranges for melamine were 0.2-10 μg·mL-1. The average recovery rate of this method varied from 80.5% to 93.5% with the relative standard deviation of 7.7% (n=9) when blank sample was fortified standard working solution of 1, 2 and 4 μg·mL-1.